Oxacillin-induced leukocytoclastic vasculitis. (2019) - Mericliler, Meric; Shnawa, Aya; Al-Qaysi, Dalya; Fleisher, Jorge; Moraco, Andrew
Abstract: Leukocytoclastic vasculitis (LCV) refers to a histopathological pattern of neutrophil predominant inflammatory process of small vessels associated with fibrinoid necrosis. Cutaneous LCV usually presents as symmetrically distributed palpable purpuric nodules of the lower extremities with or without systemic involvement. Although 50% of LCV cases are idiopathic, it can be secondary to identifiable causes such as malignancy, autoimmune conditions, infections, and medications. Medications have been implicated in up to 25% of cases; sulfonamides, NSAIDs, and beta-lactams have the most frequent association. We herein present a 32-year-old female who developed palpable purpura over hands and lower limbs 12 days after exposure to oxacillin administered for infective endocarditis. Punch biopsy from the skin lesions confirmed the diagnosis of LCV. Given the temporal relationship between oxacillin administration and development of skin findings, the diagnosis of oxacillin-associated LCV was suspected. Discontinuation of drug resulted in resolution of the lesions confirming the diagnosis. To our knowledge, this is the second case of oxacillin-induced cutaneous LCV described in literature.